Examining Neurosteroid-Analogue Therapy in the Preterm Neonate For Promoting Hippocampal Neurodevelopment - Shaw, Julia C.; Dyson, Rebecca M.; Palliser, Hannah K.; Sixtus, Ryan P.; Barnes, Heather; Pavy, Carlton L.; Crombie, Gabrielle K.; Berry, Mary J.; Hirst, Jonathan J. (Frontiers in Physiology, 2022)
Background: Preterm birth can lead to brain injury and currently there are no targeted therapies to promote postnatal brain development and protect these vulnerable neonates. We have previously shown that the neurosteroid-analogue ganaxolone promotes white matter development and improves behavioural outcomes in juvenile guinea pigs born preterm. Adverse side effects in this previous study necessitated this current follow-up dosing study, where a focus was placed upon physical wellbeing during the treatment administration and markers of neurodevelopment at the completion of the treatment period. Methods: Time-mated guinea pigs delivered preterm (d62) by induction of labour or spontaneously at term (d69). Preterm pups were randomized to receive no treatment (Prem-CON) or ganaxolone at one of three doses [0.5mg/kg ganaxolone (low dose; LOW-GNX), 1.0mg/kg ganaxolone (mid dose; MID-GNX), or 2.5mg/kg ganaxolone (high dose; HIGH-GNX) in vehicle (45% -cyclodextrin)] daily until term equivalence age. Physical parameters including weight gain, ponderal index, supplemental feeding, and wellbeing (a score based on respiration, activity, and posture) were recorded throughout the preterm period. At term equivalence, brain tissue was collected, and analysis of hippocampal neurodevelopment was undertaken by immunohistochemistry and RT-PCR. Results: Low and mid dose ganaxolone had some minor effects on early weight gain, supplemental feeding, and wellbeing, whereas high dose ganaxolone significantly affected all physical parameters during the postnatal period when compared to the preterm control neonates. Deficits in the preterm hippocampus were identified using neurodevelopmental markers including mRNA expression of oligodendrocyte lineage cells (CSPG4, MBP), neuronal growth (INA, VEGFA), and the GABAergic/glutamatergic system (SLC32A1, SLC1A2, GRIN1, GRIN2C, DLG4). These deficits were not affected by ganaxolone at the doses used at the equivalent of normal term. Conclusion: This is the first study to investigate the effects of a range of doses of ganaxolone to improve preterm brain development. We found that of the three doses, only the highest dose of ganaxolone (2.5mg/kg) impaired key indicators of physical health and wellbeing. Whilst it may be too early to see improvements in markers of neurodevelopment, further long-term study utilising the lower doses are warranted to assess functional outcomes at ages when preterm birth associated behavioural disorders are observed.